Antitumor Activities of Kushen: Literature Review. (28th August 2012) - Sun, Mingyu; Cao, Hongyan; Sun, Lin; Dong, Shu; Bian, Yanqin; Han, Jun; Zhang, Lijun; Ren, Shuang; Hu, Yiyang; Liu, Chenghai; Xu, Lieming; Liu, Ping
Abstract : To discover and develop novel natural compounds with therapeutic selectivity or that can preferentially kill cancer cells without significant toxicity to normal cells is an important area in cancer chemotherapy. Kushen, the dried roots of Sophora flavescens Aiton, has a long history of use in traditional Chinese medicine to treat inflammatory diseases and cancer. Kushen alkaloids (KS-As) and kushen flavonoids (KS-Fs) are well-characterized components in kushen. KS-As containing oxymatrine, matrine, and total alkaloids have been developed in China as anticancer drugs. More potent antitumor activities were identified in KS-Fs than in KS-As in vitro and in vivo . KS-Fs may be developed as novel antitumor agents.